2019
DOI: 10.1155/2019/4035460
|View full text |Cite
|
Sign up to set email alerts
|

ANXA2 Silencing Inhibits Proliferation, Invasion, and Migration in Gastric Cancer Cells

Abstract: Annexin A2 (ANXA2) has been well known to associate with the progress of malignant tumor. However, the biological behavior of ANXA2 in gastric cancer (GC) remains unclear. We made a hypothesis in transcriptome level from TCGA datasets. Then, we used immunohistochemical staining to quantify the expression level of ANXA2 protein in GC tissues compared with adjacent tissues. Quantitative real-time PCR and western blot were used for analyzing ANXA2 expression in human GC (SGC-7901, MKN-45, BGC-823, and AGS) cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…ANXA2 has recently been linked to the metastasis of several types of cancer, such as prostate [ 27 ], colorectal [ 28 ], and breast cancer [ 29 ]. High expression of ANXA2 promotes the development of GC and is negatively correlated with the clinical prognosis [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…ANXA2 has recently been linked to the metastasis of several types of cancer, such as prostate [ 27 ], colorectal [ 28 ], and breast cancer [ 29 ]. High expression of ANXA2 promotes the development of GC and is negatively correlated with the clinical prognosis [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that VEGF and IL-6 were highly expressed in GC and promoted the occurrence and development of GC by promoting angiogenesis and maintaining continuous uncontrollable inflammatory response [ 31 ]. Here, we analyzed the relationship between SERPINE1 expression and VEGF and IL-6 to explore the possible mechanism in GC.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor metastasis is the result of many factors, and the process is more complex, including cancer cells entering the blood, invading lymph nodes, transiting through the tumor microenvironment, aggregating and secondary tissues, etc. Cancer cell migration plays an important role in the process of tumor metastasis, but the specific mechanism has not been determined and needs further studied [ 31 ], p. 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ANXA2, a member of the annexin family, mainly participates in cytoskeleton rearrangement and plasminogen activation [20]. Accumulated evidence has indicated that ANXA2 expressed on the cell membrane of gastric cancer cells was important to maintain the malignancy of cells and becomes a potential prognostic marker in gastric cancer [21][22][23][24]. Overexpression of ANXA2 has been reported in gastric epithelial cells following H. pylori infection, indicating its involvement in H. pylori pathogenesis [25].…”
Section: Biomed Research Internationalmentioning
confidence: 99%